2009
DOI: 10.1002/cne.22052
|View full text |Cite
|
Sign up to set email alerts
|

Conditional ablation and recovery of forebrain neurogenesis in the mouse

Abstract: Forebrain neurogenesis persists throughout life in the rodent subventricular zone (SVZ) and hippocampal dentate gyrus (DG). Several strategies have been employed to eliminate adult neurogenesis and thereby determine whether depleting adult-born neurons disrupts specific brain functions, but some approaches do not specifically target neural progenitors. We have developed a transgenic mouse line to reversibly ablate adult neural stem cells and suppress neurogenesis. The nestin-tk mouse expresses herpes simplex v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 87 publications
5
49
0
Order By: Relevance
“…To address this question, we have examined LTP in the nestinthymidine kinase (nestin-tk) mouse model, in which herpes simplex virus (HSV) thymidine kinase expression is regulated by the nestin enhancer, enabling the specific and temporally controlled ablation of neurogenesis after the intracerebroventricular administration of ganciclovir (GCV). In this model, treatment with GCV for 28 d results in nearly complete suppression of neurogenesis in youngadult mice (26). Consistent with previous results, we found that LTP was significantly disrupted when assessed immediately following ablation.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…To address this question, we have examined LTP in the nestinthymidine kinase (nestin-tk) mouse model, in which herpes simplex virus (HSV) thymidine kinase expression is regulated by the nestin enhancer, enabling the specific and temporally controlled ablation of neurogenesis after the intracerebroventricular administration of ganciclovir (GCV). In this model, treatment with GCV for 28 d results in nearly complete suppression of neurogenesis in youngadult mice (26). Consistent with previous results, we found that LTP was significantly disrupted when assessed immediately following ablation.…”
supporting
confidence: 92%
“…These results suggest that the LTP deficit seen in nestin-tk mice treated with GCV is specific to the loss of newborn DGCs. Recent work suggests that 28 d of GCV treatment in nestin-tk mice results in a loss of newborn DGCs that persists for at least 42 d (6 wk) after the discontinuation of the GCV infusion (26). To determine the impact of persistently suppressed neurogenesis on LTP, experiments similar to those described above (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of TK renders the cell population of interest susceptible to the cytotoxic effect of GCV (36). Studies to date have used either GFAP (20)(21)(22) or nestin (23) to direct the expression of TK. GFAP is a type III intermediate filament protein expressed classically in astrocytes, including SVZ astrocytes that give rise to neurons (37) and oligodendrocytes (38).…”
Section: Resultsmentioning
confidence: 99%
“…Several techniques have been used for this purpose, including x-irradiation (7)(8)(9)(10)(11)(12)(13), antimitotic (4,(14)(15)(16)(17)(18) or other antiproliferative (19) drugs, and conditional transgenic targeting of selected [glial fibrillary acidic protein (GFAP)-, nestin-, or homolog of Drosophila taillessexpressing] cell populations with HSV-1 thymidine kinase (TK) (20)(21)(22)(23) or inducible recombination (24). However, studies that use these ablation techniques to assess the functional significance of neurogenesis can be difficult to interpret, because ablation may be accompanied by inflammatory responses with microglial activation (7), alterations in microvascular anatomy (7), systemic toxicity (18), or involvement of nonneuronal cell lineages (25).…”
mentioning
confidence: 99%
“…Indeed, it was shown that animals with blocked adult neurogenesis do not recover from depressionlike behavior when chronically administered with ADs (Santarelli et al, 2003;Surget et al, 2008;David et al, 2009;Onksen et al, 2011;Perera et al, 2011). However, recent studies suggest both neurogenesis-dependent and independent mechanisms underlying ADs action, as more studies show none or only partial effect of reducing neurogenesis on restoration of behavioral homeostasis by ADs (Meshi et al, 2006;David et al, 2007;Holick et al, 2008;Surget et al, 2008;Bessa et al, 2009a;David et al, 2009;Singer et al, 2009;Nollet et al, 2012).…”
Section: Introductionmentioning
confidence: 99%